Efforts to Improve Nutrition for Children in Teluk Bakung Village, Tanjung Pura District, Langkat Regency - Wirman, Wirman; Afiva, Nazwa; Nazwa, Windy Sakila (CV. Rayyan Dwi Bharata, 2024)
This research aims to evaluate efforts to improve nutrition for children in Teluk Bakung Village, District. Tanjung Pura. The method used is descriptive qualitative which carries out direct observations in the field. The research results show that the nutrition improvement program provided includes providing additional feeding and regular monitoring of children's health. The main thing to prevent stunting is by providing improved nutrition, starting from the womb.